1991
DOI: 10.1056/nejm199105303242201
|View full text |Cite
|
Sign up to set email alerts
|

The Beneficial Effects of Early Dexamethasone Administration in Infants and Children with Bacterial Meningitis

Abstract: The results of this study, in which dexamethasone administration began before the initiation of cefotaxime therapy, provide additional evidence of a beneficial effect of dexamethasone therapy in infants and children with bacterial meningitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
153
1
14

Year Published

1991
1991
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 459 publications
(172 citation statements)
references
References 22 publications
4
153
1
14
Order By: Relevance
“…It is possible that better management of the complications and the earlier use of proper antibiotics could be related to the decreased mortality rate observed in our cases. In trial studies in children with bacterial meningitis, dexamethasone has been shown to reduce meningeal inflammation and improve the outcome of disease 4 -5 -7 ' 8 . Corticosteroids have been utilized systematically as an additional therapy in children with bacterial meningitis admitted to our hospital.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that better management of the complications and the earlier use of proper antibiotics could be related to the decreased mortality rate observed in our cases. In trial studies in children with bacterial meningitis, dexamethasone has been shown to reduce meningeal inflammation and improve the outcome of disease 4 -5 -7 ' 8 . Corticosteroids have been utilized systematically as an additional therapy in children with bacterial meningitis admitted to our hospital.…”
Section: Discussionmentioning
confidence: 99%
“…Odio et al 7 noted a decrease in hearing deficit after steroid therapy in patients with Haemophilus influenza type B meningitis in infants 6 weeks to 13 years. Ciana et al 8 in his study in children living in developing countries reported the same beneficial effect of steroids.…”
Section: Discussionmentioning
confidence: 99%
“…The contrast between the two clusters was also estimated as a measure of the effect of "CSF inflammation" on the outcomes. The following further independent variables were considered in multivariate analysis: age; sex; time (days) elapsed since first symptoms (any) to admission; use of antibiotics (any) before the diagnosis of meningitis; presence of serious comorbidity [includes malignancy, immunodeficiency (immunosuppressants, human immunodeficiency virus infection or splenectomy), diabetes mellitus (DM), other endocrinological diseases, alcohol abuse and liver cirrhosis, other chronic organ diseases (lungs, heart, kidney, liver)]; presence of focal neurological symptoms on admission (includes aphasia, cranial nerve palsy, monoparesis or hemiparesis); leukocyte count on admission; pathophysiological mechanism of the disease (e.g., meningitis following septicemia, or following middle ear infection or trauma; dichotomized as "following septicemia" and "other"); microbiologically verified BM (considered as yes/no, and also as pneumococcal/other bacterial/probable); worst Glasgow Coma Score (GCS) within 24 hours since admission as a continuous variable and also categorized into levels of consciousness disturbance as: none (GCS ≥15), mild (GCS [13][14], moderate (GCS 10-12 ) or severe (GCS ≤9); and timing of the appropriate antibiotic treatment (empirical as per in-house guidelines, or bacteriologically targeted, see above) commencement specifically in relation to the onset of consciousness disturbance and/or overt meningitis symptoms (e.g., fever, headache, vomiting, malaise) (16). Namely, although the "door-to-antibiotic" delay negatively affects the outcomes in community-acquired adult BM (particularly if > 2hours), timing of the appropriate antibiotic treatment relative to the onset of consciousness disturbance and/or other specific meningitis symptoms appears to be a particularly relevant predictor of the disease outcome (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…The decision to introduce adjunctive dexamethasone in treatment of adult BM 20 years ago was based on the then existing reports of its favourable effects in pediatric Haemophilus influenzae type B meningitis (12,13). Dexamethasone was to be used in patients with clinical and CSF signs supporting the diagnosis of BM, except those with a recent history (within a month before admission for meningitis) of upper gastrointestinal bleeding or peptic ulcer.…”
Section: Antibiotic Treatment and Treatment With Dexamethasonementioning
confidence: 99%